Oficinas de leitura literária a partir de "Os Sertões", de Euclides da Cunha - Duarte, Alexandra Cardoso da Silva (2019)
This Course Completion Work is composed of a report and a literary reading tutorial. This work aims to contribute to the teaching of literary reading, from a cultural perspective that recognizes the particularities of the identities of the work and the reader. In this sense, the work intends to expand the teaching of literature at school, allying it to multimodality, developing a practice that incorporates the precepts of digital literacy. This project was developed with ninth grade students from a municipal school, located in the urban area of Monte Santo - BA. As a corpus of the research, was selected the chapter The struggle, of Os sertões, for an approach of cultural and aesthetic reading, having as central proposal, to build a tutorial of literary reading that configure in an instrument that allows the reading of the literary text, contemplating the multimodality, present in the perspective of the multiletramentos of Roxane Rojo (2012) and the digital literacy of Freitas (2010). The tutorial was developed, mixing the narrative of Euclides da Cunha with the comic book, images and video options about the work. The analysis of the literary text will be based on the cultural model of reading by Carlos Gomes (2012) which privileges the training of a critical reader and his cultural heritage, and subjective reading by Annie Rouxel (2013) which deals with the importance of aesthetic experience in the training of the reader. The work brings in its composition literary workshops that are divided into three stages: memories that aim to discuss what minorities students have about the Canudos War; multiletramentos that intends to present other possibilities to work with the narrative of The Sertões; cultural model of reading that makes a re-reading of the representations of the Canudos War, from the intersection between the aesthetic and the political and promotes a critical reading of what led and maintained the fight in Canudos. Following is a tutorial that includes a reading script from the part The Struggle of the Work The Backlands and instructions for setting up a literary reading workshop that focuses on expeditions to Canudos.